The underlying mechanism of partial anterior cruciate ligament injuries to the meniscus degeneration of knee joint in rabbit models - Dalin Wang; Zhe Wang; Mingcheng Li; Songbao Xu (Journal of Orthopaedic Surgery and Research, 2020)
Abstract Background The diagnosis, treatment, and efficacy evaluation of anterior cruciate ligament (ACL) partial rupture remains controversial. This research aims to investigate the underlying mechanism of partial ACL injuries to the meniscus degeneration in the rabbit knee. Methods Sixty New Zealand white rabbits were randomly divided into three groups including an experimental group, a sham group (n = 6), and a blank control group (n = 6). The experimental group is composed of an anteromedial bundle (AMB) rupture group (n = 24) and a posterolateral bundle (PLB) rupture group (n = 24). Rabbits in the experimental group were subjected to right hind limbs knee surgery to induce ACL part injury under the arthroscopy. Finally, eight rabbits including 6 in the model group and 2 in the control group were sampled randomly on the 2nd, 4th, and 8th weeks respectively. We observed the typical form of the meniscus through HE staining. Expressions of inflammatory factors including interleukin-1β (IL-1β) and IL-17 in the knee joint fluid were determined by means of an ELISA. Analysis of the mRNA expressions of matrix metalloproteinases-13(MMP-13) was performed to evaluate the inflammatory mediators in the pathogenesis of the meniscus. Results HE staining results showed that the surface was rough and the tissues were loose displaying collagen fibers of varying thickness. Both IL-1β and IL-17 in the synovial fluid and the positive rate of MMP-13 in addition to MMP-13 mRNA showed a demonstrable increase treads from the 2nd to the 8th week. The significant difference was found (P < 0.05) compared to the control group. Conclusion We conclude that the elevated levels of IL-1β and IL-17, along with increased MMP13 expression, resulted in meniscus degradation in the rabbit knee joint model with partial ACL injury.